A Perspective on Indigo: An Iconic Colorant - Anthony Harriman (Colorants)
This perspective sets out to raise awareness about the chemical and photophysical properties of indigo, a highly distinguished colorant with an extraordinary history. Indigo, like many other dyes, was first extracted from plants at an inordinately low yield and at great ecological expense. Such was its popularity that indigo was among the first natural colorants to be synthesized in a laboratory before refinement and cost reduction resulted in its economical industrial-scale production. The color of indigo is highly characteristic but difficult to describe, since it falls at the blue/violet interface. It is a small, planar molecule with an exceptionally high degree of π-electron conjugation that pushes the absorption maximum to above 600 nm. Its structure helps explain the high level of photostability enjoyed by indigo, while recent spectroscopic studies have added to our understanding of the longevity of this emblematic colorant. The reversible formation of leuco-indigo increases the ways in which indigo can be used to add color to objects while helping to circumvent the effects of attack by free radicals. It is stressed that the journal Colorants would welcome submissions that describe the chemistry and/or spectroscopy of other representative colorants.